Mixing dynamics control in RIM machines - Ertugrul Erkoç (2007)
A novel control scheme for assessing mixing on reaction injection moulding is introduced and the results of its implementation are presented. The control scheme is based on the dynamic measurement of static pressure in the feeding lines to the mixing chamber injectors. The pressure signal oscillates with a frequency which allows assessing the flow regime inside the mixing chamber. Here, the pressure signal frequencies are C compared with flow field data inside the mixing chamber obtained from computational fluid dynamics simulations, laser Doppler anemometry and particle image velocimetry measurements.